I like stars - Brown, Margaret Wise, 1910-1952.; Paley, Joan (New York : Golden Books, 1998)
A simple poem describing all kinds of stars that appear in the night sky.
BR
Keywords: Stars -- Juvenile poetry; Children's poetry, American; Stars -- Poetry; American poetry